Austria : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Securities Regulation, Insurance Regulation, and Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2004)
Austria's Financial System Stability Assessment highlights Reports on the Observance of Standards and Codes on banking supervision, securities regulation, and insurance regulation. The banking sector has weathered the recent economic slowdown well, and is generally sound and resilient. Austria enjoys a high standard of supervision based on strong institutions and a comprehensive legal framework. Ongoing reforms and European Union directives in the pipeline will address most of the identified gaps in observance of financial sector standards and codes.